Preventive effect of an ethanolic avocado on apoptosis induced via oxidative damage in albino rats tissues - Al-Hayyali, Fatimah Qasim Mohammed; Khalaf , Aljuboury Maha (Acta Scientiarum. Animal Sciences, 2024)
Oxidative stress is the result of an imbalance between the production of oxidant precursors and the capacity of antioxidant defense. Oxygen free radicals play an important role in causing diseases. In this study, the protective effect of ethanolic avocado on apoptosis caused by oxidative damage in the tissue of albino rats was investigated. 24 male albino rats of the Faculty of Veterinary Medicine in Mosul, Iraq, which were kept in standard conditions for at least 10 days before and through the experimental work, were examined. Four groups of rats include the control group (healthy group), the group of male rats with ethanolic avocado consumption; The third group of male rats that were treated with 0.5% of hydrogen peroxide H2O2; and the fourth group of male rats that were treated with both 0.5% H2O2 and avocado ethanolic extract (50 mg kg-1 BW) for four weeks. After fixing the tissues of the liver, kidney, lung, spleen and testis in 10% buffered formalin, they were stained with hematoxylin. TUNEL assay was performed using the TUNEL cell death assay kit to detect apoptotic cells. In this investigation, the histology results in four groups of rats showed that in the rats that were treated with avocado, there were minor tissue changes in their liver, kidney, and intestine, and the tissues of these organs were healthy. In TUNEL staining, it was also shown that there are no apoptotic cells in the liver, kidney and testis cells in avocado-treated rats. The results showed that ethanolic Avocado is useful against oxidative stress damage and it may be used to protect tissues against oxidative stress.